2021
DOI: 10.3892/mmr.2021.11989
|View full text |Cite
|
Sign up to set email alerts
|

Berberine ameliorates the LPS-induced imbalance of osteogenic and adipogenic differentiation in rat bone marrow-derived mesenchymal stem cells

Abstract: Lipopolysaccharide (LPS) from oral pathogenic bacteria is an important factor leading to alveolar bone absorption and the implant failure. The present study aimed to evaluate the modulation of berberine hydrochloride (BBR) on the LPS-mediated osteogenesis and adipogenesis imbalance in rat bone marrow-derived mesenchymal stem cells (BMSCs). Cell viability, osteoblastic and adipogenic differentiation levels were measured using the Cell Counting Kit-8 assay, alkaline phosphatase (ALP) staining and content assay, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…BBR has been widely studied due to its anti-inflammatory, antioxidant, antibacterial and immune regulation properties [ [51] , [52] , [53] ]. Recent studies have shown that BBR can promote the osteogenesis of BMSCs [ 27 , 28 , 32 ]. Similar to KGN, the stable molecular structure of BBR facilitates in vitro manipulation and encapsulation by various materials and maintains biological activity in the control release process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BBR has been widely studied due to its anti-inflammatory, antioxidant, antibacterial and immune regulation properties [ [51] , [52] , [53] ]. Recent studies have shown that BBR can promote the osteogenesis of BMSCs [ 27 , 28 , 32 ]. Similar to KGN, the stable molecular structure of BBR facilitates in vitro manipulation and encapsulation by various materials and maintains biological activity in the control release process.…”
Section: Resultsmentioning
confidence: 99%
“…Berberine (BBR) has been reported to induce BMSCs osteogenesis and inhibit OA progression in animal models [ [27] , [28] , [29] , [30] ]. Moreover, the antioxidant and anti-inflammatory properties of BBR are expected to inhibit oxidative stress-induced apoptosis and maintain the differentiation potentials of BMSCs under the inflammatory environment of injured joints [ 31 , 32 ]. Besides, the hydrophobicity of KGN and BBR allows them to be efficiently encapsulated in SF nano- and microspheres using a simple, rapid and scalable method described by Wang et al., thereby realizing long-term sustained release [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…For adipogenic differentiation, MSCs were incubated in a DMEM supplemented with 1 µM dexamethasone, 0.5 mM isobutylmethylxanthine, 10 nM insulin and 100 µM indomethacin at 37 °C for 12 days, and the media were changed every 3 days. Then, the cells were harvested for oil red O staining [ 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…6 Moreover, lipopolysaccharides also impair osteoblast differentiation and suppress osteogenic differentiation tendency of BMSCs. 7 Suppression of lipopolysaccharide-stimulated inflammation and differentiation in BMSCs contributed to the amelioration of immuno-inflammatory oral diseases. 8 Galangin is a natural flavonoid extracted from Alpinia officinarum with pharmacological activities, such as anticancer, antibacterial, anti-inflammatory, hepatoprotective, and antiarthritic effects.…”
Section: Introductionmentioning
confidence: 99%